A mandioca no Brasil - Fukuda, Wania Maria Gonçalves; Porto, M.C.M. (International Center for Tropical Agriculture, 1991)
The current status of cassava cultivation in Brazil is analyzed; aspects covered are the distribution of production, cultivation systems, main uses given to the crop, and problems encountered in the different geographic regions of the country (north, NE, SE, south, and central-west). An overview is also provided of the current structure of research and its potential in the areas of plant breeding and germplasm use; an historical overview is given and the status of different research projects is detailed. Conclusions indicate that production constraints vary from one region to another, but in most of them, cassava is grown without the use of improved technology. This lack of adoption reflects in part the lack of credit facilities and the limited market due to the reduced no. of products, the restricted demand, and unfavorable competition with products favored with the national agricultural policy. The creation of the Centro Nacional de Pesquisa de Mandioca e Fruticultura unified plant breeding research at the national level. (CIAT)